Pengaruh Kualitas Sumber Daya Manusia, Pemanfaatan Teknologi Informasi Dan Pengawasan Keuangan Daerah Terhadap Keandalan Penyajian Laporan Keuangan Pemerintah Daerah (Studi pada OPD Pemerintah Provinsi Sulawesi Tengah) - Latifah Sukmawati Yuniar; Arif Gunarsa; Faizal Asdar; Galing Ralis; Aulia Putri Ramadhani; Daud Ruranto Buntulabi (Politeknik Ganesha Medan, 2023)
The existence of increasing demands for the implementation of public accountability has implications for management in government agencies to provide information to the public, one of which is information in financial reports. Government financial reports are an important component in realizing financial management accountability to the public. The function of information in financial reports will not have benefits if the presentation and delivery of financial information is not reliable. Reliability of financial report information is a manifestation of public financial management accountability and in accordance with Government Regulation Number 24 of 2005 is an element of important information value related to decision-making of various parties. This type of research is associative. This study aims to explain the influence of the quality of human resources, the use of information technology and regional financial supervision on the reliability of the presentation of regional financial reports in the OPD of the Central Sulawesi Provincial Government. Based on the results of data analysis that has been carried out to test the hypotheses put forward in this study, several conclusions can be drawn, including: The quality of human resources has a positive effect on the reliability of financial statement presentation accepted and supported by empirical evidence. Acceptance or proof of the first hypothesis simultaneously answers the first research question. Utilization of information technology has a positive effect on the reliability of presentation of acceptable financial statements. Accepting or proving this second hypothesis, this also answers the second research question. Regional financial supervision has a positive effect on the reliability of presentation of financial statements is accepted so that the hypothesis can be accepted and is supported by empirical evidence. Acceptance or proof of this third hypothesis simultaneously answers the research question.